2010
DOI: 10.1002/nau.20897
|View full text |Cite
|
Sign up to set email alerts
|

New strategies of pelvic nerves stimulation for recovery of pelvic visceral functions and locomotion in paraplegics

Abstract: This short series indicated that laparoscopic implantation of neuroprothesis to the pelvic nerves offers absolutely new strategies based on new combinations of various reported methods to enhance bladder functions and to recover some locomotion in paraplegics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 19 publications
1
40
0
Order By: Relevance
“…Operative technique After the patient signed informed consent form for surgery and permissions (for case details, personal information and images), he underwent the LION procedure in June 2011 in accordance with the technique described previously: 4 The procedure consisted of the implantation, by laparoscopy, of fine wire (designed for spinal cord stimulation or for sacral nerve root stimulation) in direct contact to the endopelvic portion of the somatic pelvic nerves for electrical stimulation or neuromodulation. An epidural spinal cord stimulation unit (Restore ADVANCED, Medtronic, Minneapolis, MN, USA) and four 4-arrays fine wire electrodes were implanted to the sciatic, pudendal and femoral nerves according to our surgical technique described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Operative technique After the patient signed informed consent form for surgery and permissions (for case details, personal information and images), he underwent the LION procedure in June 2011 in accordance with the technique described previously: 4 The procedure consisted of the implantation, by laparoscopy, of fine wire (designed for spinal cord stimulation or for sacral nerve root stimulation) in direct contact to the endopelvic portion of the somatic pelvic nerves for electrical stimulation or neuromodulation. An epidural spinal cord stimulation unit (Restore ADVANCED, Medtronic, Minneapolis, MN, USA) and four 4-arrays fine wire electrodes were implanted to the sciatic, pudendal and femoral nerves according to our surgical technique described previously.…”
Section: Methodsmentioning
confidence: 99%
“…laparoscopic implantation of neural electrode (implant below the level of the injury) to restore the motor or autonomic function (37,38).…”
Section: Sexual Dysfunctionsmentioning
confidence: 99%
“…One problem is an overactive bladder causing urinary incontinence and this is managed through bladder inhibition. Possover et al, [28], using a bladder control system, showed in three SCI patients that pudendal nerve stimulation at 20 Hz could inhibit the bladder producing bladder filling volumes of 500 ml. Another problem for SCI patients is high urethral resistance; Possover et al, [28] demonstrated in one patient that a 1.2 KHz high-frequency blocking of the pudendal nerve could be used to decrease urethral resistance.…”
Section: Implantable Bladder Stimulators and Proposed Development Workmentioning
confidence: 99%
“…Possover et al, [28], using a bladder control system, showed in three SCI patients that pudendal nerve stimulation at 20 Hz could inhibit the bladder producing bladder filling volumes of 500 ml. Another problem for SCI patients is high urethral resistance; Possover et al, [28] demonstrated in one patient that a 1.2 KHz high-frequency blocking of the pudendal nerve could be used to decrease urethral resistance. In this study, we tested high-frequency blocking methods on the pudendal nerve, the results are reported in a parallel study publication [29].…”
Section: Implantable Bladder Stimulators and Proposed Development Workmentioning
confidence: 99%